Spectrum of cutaneous lupus erythematosus in South Africans with systemic lupus erythematosus. (July 2019) - Koch, K; Tikly, M
Background: Cutaneous involvement is very common in systemic lupus erythematosus. We describe the prevalence and spectrum of lupus-specific (cutaneous lupus erythematosus) and non-specific cutaneous features amongst mostly black South Africans with systemic lupus erythematosus. Patients and methods: A retrospective record review of 298 South Africans (262 blacks and 36 non-blacks) with systemic lupus erythematosus was carried out. Cutaneous features were classified according to the Gilliam and Sontheimer classification of cutaneous lupus. Results: Most (81.5%) patients were black African females. The mean (SD) age at diagnosis and follow-up duration were 35.0 (11.8) and 8.0 (5.9) years, respectively. Cutaneous lupus erythematosus was seen in 76.1% of patients, mainly chronic cutaneous lupus erythematosus with the discoid lupus erythematosus subtype seen in 52.1% of patients. Acute cutaneous lupus erythematosus was seen in 30.2% of patients and was more common in non-blacks than blacks (odds ratio = 3.8 (1.9–7.9)); localized acute cutaneous lupus erythematosus was more common than generalized acute cutaneous lupus erythematosus (odds ratio = 2.6 (1.6–4.4)). Non-specific cutaneous features occurred in 77.2%, with oral/nasal ulcers and Raynaud's phenomenon each occurring in approximately 40% of patients. Diffuse melanonychia at initial diagnosis was present in 37.4% of patients and was more common in blacks than non-blacks (odds ratio = 3.1 (1.3–7.3)). Acute cutaneous lupus erythematosus was associated with renal disease (odds ratio = 2.8 (1.6–4.7)) and chronic cutaneous lupus erythematosus with arthritis (odds ratio = 2.02 (1.24–3.29)). Diffuse melanonychia was associated with less renal disease and anti-dsDNA antibody positivity (odds ratio = 0.4 (0.3–0.7) and 0.4 (0.2–0.6), respectively) and significantly lower lupus severity index scores (mean (SD) = 5.99 (1.11) vs 6.56 (1.36) in patients with no melanonychia, p < 0.05)). Conclusion: In this study of South Africans with systemic lupus erythematosus, the skin was the most commonly affected organ. In general, cutaneous lupus erythematosus was associated with less severe systemic disease. Acute cutaneous lupus erythematosus was less common in blacks, whereas discoid lupus erythematosus was more common than reported in Caucasians. Diffuse melanonychia was a distinctive finding and was associated with milder systemic disease.